Association of diagnostic delay with medical cost for patients with Crohn's disease: A Japanese claims‐based cohort study. Issue 5 (24th March 2021) - Takeyama, Eisuke; Wada, Hiroo; Sato, Setsuko; Tomooka, Kiyohide; Ikeda, Ai; Tanigawa, Takeshi
Abstract: Background and Aim: Longer diagnostic delay (DD) in Crohn's disease (CD) is associated with complications and related surgeries. However, the impact of DD on medical cost after CD diagnosis remains uncertain. Methods: This was a claims‐based cohort study. Our analysis used data from 2005 to 2018 from the Japanese Claims Database. We enrolled a total of 528 newly diagnosed CD patients (76.9% male) aged 31.5 ± 13.6 years. High medical cost was defined as the highest quartile of the average monthly medical cost. DD was defined as the interval between the first visit to a gastroenterologist and diagnosis with CD. In the multivariable logistic regression analysis, patients were stratified by the use of anti‐tumor necrosis factor alpha (anti‐TNFα) agents to exclude their influence on the observed effects. This study was approved by the ethics review board of the Juntendo University Faculty of Medicine (No. 2019178). Results: The multivariable‐adjusted odds ratios and 95% confidence intervals of high medical cost were 1.41 (0.81–2.43) and 0.91 (0.57–1.46), respectively, for a DD of >12 months and 1 to ≤12 months compared to <1 month. In patients receiving anti‐TNFα agents, the multivariable‐adjusted odds ratios for high medical cost were 2.63 (1.34–5.16) and 1.35 (0.79–2.28) for a DD of >12 months and 1 to ≤12 months, respectively, compared to <1 month. In patients without anti‐TNFα, multivariable logistic regression analyses were not presented because of a small number of patients categorized into the high medical cost group. Conclusion: A delayed diagnosis of CD may incur high medical cost in patients who develop aggressive disease that requires treatment with anti‐TNFα agents. Abstract : This was a claim‐based cohort study that assessed the association between the diagnostic delay (DD) and medical cost in patients with Crohn's disease. As a result, the association between longer DD over 12 months and high medical cost defined as the highest quartile of average monthly medical cost was found in patients treated with anti‐tumor necrosis factor a agents.